2014
DOI: 10.1111/jace.13170
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Thermophysical Properties of Stoichiometric CeO2 in Comparison to UO2 and PuO2

Abstract: The thermal conductivity of stoichiometric CeO2 was determined through measurement of thermal expansion from 313 to 1723 K, thermal diffusivity from 298 to 1473 K, and specific heat capacity from 313 to 1373 K. The thermal conductivity was then calculated as the product of the density, thermal diffusivity, and specific heat capacity. The thermal conductivity was found to obey an (A + BT)−1 relationship with A = 6.776×10−2 m·K·W−1 and B = 2.793 × 10−4 m·W−1. Extrapolations of applied models were made to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 49 publications
5
49
0
Order By: Relevance
“…Venkata et al [37], and Arita et al [14] to the C p versus temperature curves computed using the model for U 1Ày Ce y O 2.00 . Good agreement is seen with the results of [14] and [1]; however, the data from Venkata et al [37] are too high and deviate from the trend of decreasing C p with increasing Ce content. The model for U 1Ày Ce y O 2±x predicts higher C p values with decreasing O/M; since sealed aluminum crucibles were used in Refs.…”
Section: Thermochemical Datasupporting
confidence: 81%
See 3 more Smart Citations
“…Venkata et al [37], and Arita et al [14] to the C p versus temperature curves computed using the model for U 1Ày Ce y O 2.00 . Good agreement is seen with the results of [14] and [1]; however, the data from Venkata et al [37] are too high and deviate from the trend of decreasing C p with increasing Ce content. The model for U 1Ày Ce y O 2±x predicts higher C p values with decreasing O/M; since sealed aluminum crucibles were used in Refs.…”
Section: Thermochemical Datasupporting
confidence: 81%
“…A literature review revealed studies reporting oxygen potentials ðm O2 Þ for U 1Ày Ce y O 2±x [4e13], which are summarized in Table 1, along with molar heat capacity (C p ) measurements for stoichiometric U 1Ày Ce y O 2.00 [1,14,15]. Lorenzelli and Touzelin [8], Markin et al [16], and Hoch and Furman [6] used X-ray diffraction (XRD) to determine the phase relations in the vicinity of the fluorite U 1Ày Ce y O 2±x solution.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is, therefore, important to consider how such changes to the host lattice could alter fission gas behaviour and impact fuel performance. The use of Ce as a surrogate for Pu [10] or U [11] means CeO 2 is also of interest.…”
Section: Introductionmentioning
confidence: 99%